Development of Formula Varsity Race Car Chassis - ABDULLAH, Mohd Azman; Mansor, Muhd Ridzuan; Tamaldin, Noreffendy; Thanaraj, Krishnan (IOP Publishing, 2013)
Three chassis designs have been developed using commercial computer aided design (CAD) software. The design is based on the specifications of UTeM Formula VarsityTM 2012 (FV2012). The selection of the design is derived from weighted matrix which consists of reliability, cost, time consumption and weight. The score of the matrix is formulated based on relative weighted factor among the selections. All three designs are then fabricated using selected materials available. The actual cost, time consumption and weight of the chassis’s are compared with the theoretical weighted scores. Standard processes of cuttings, fittings and welding are performed in chassis mock up and fabrication. The chassis is later assembled together with suspension systems, steering linkages, brake systems, engine system, and drive shaft systems. Once the chassis is assembled, the studies of driver’s ergonomic and part accessibility are performed. The completion in final fittings and assembly of the race car and its reliability demonstrate an outstanding design for manufacturing (DFM) practices of the chassis.